2014
DOI: 10.1111/avj.12208
|View full text |Cite
|
Sign up to set email alerts
|

Bovine viral diarrhoea virus (‘pestivirus’) in Australia: to control or not to control?

Abstract: BVDV is endemic in Australian cattle populations, with more than 80% of herds surveyed showing some level of exposure to the pathogen. The cost to the national industry is estimated to be AUD57.9 million annually. This review identifies and discusses the challenges to BVDV control in Australia, including farmer attitudes, herd size, sheep as a potential reservoir host and diagnostic capabilities. We conclude that systematic BVDV control in Australia is, or soon will be, an option; however, detailed cost-benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 59 publications
3
30
0
1
Order By: Relevance
“…12,13 The finding is also in agreement with previous reports of worldwide BVDV antibody prevalence in cattle ranging from 0-90%. 9 All of the grouping factors which were investigated for their interaction with the BVDV prevalence in the current study have shown significant association.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…12,13 The finding is also in agreement with previous reports of worldwide BVDV antibody prevalence in cattle ranging from 0-90%. 9 All of the grouping factors which were investigated for their interaction with the BVDV prevalence in the current study have shown significant association.…”
Section: Discussionsupporting
confidence: 92%
“…12,13 The lower seroprevalence in calves could also be due to some of the calves investigated might be PI animals which are known to be immunotolerant to the virus and do not produce antibody against the virus to be detected by the ELISA Ab test. According to Fulton et al 4 the prevalence of PI animals in South Central United States was revealed to be 0.55%, while Houe et al 22 recorded the prevalence of PI animals in Michigan (USA) to be 0.13%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of BVDV in Australian cattle herds has been recently reported to be as high as 80% . Losses to the Australian cattle industry caused by BVDV infection are estimated to be at least A$114.4 million, prompting discussion on the feasibility of systematic BVDV control programs in Australia . The ability of non‐bovine species to maintain BVDV infection and act as a reservoir host has been identified as a possible threat to control efforts .…”
mentioning
confidence: 99%
“…The annual cost of BVDV in the Australian cattle population was estimated to be AUS $57.9 million (Lanyon and Reichel, ).…”
Section: Assessmentmentioning
confidence: 99%